TSPEAR variants are primarily associated with ectodermal dysplasia and tooth agenesis but not hearing loss: A novel cohort study. Issue 8 (27th May 2021) - Bowles, Bradley; Ferrer, Alejandro; Nishimura, Carla J.; Pinto e Vairo, Filippo; Rey, Tristan; Leheup, Bruno; Sullivan, Jennifer; Schoch, Kelly; Stong, Nicholas; Agolini, Emanuele; Cocciadiferro, Dario; Williams, Abigail; et al.
Abstract: Biallelic loss‐of‐function variants in the thrombospondin‐type laminin G domain and epilepsy‐associated repeats ( TSPEAR ) gene have recently been associated with ectodermal dysplasia and hearing loss. The first reports describing a TSPEAR disease association identified this gene is a cause of nonsyndromic hearing loss, but subsequent reports involving additional affected families have questioned this evidence and suggested a stronger association with ectodermal dysplasia. To clarify genotype–phenotype associations for TSPEAR variants, we characterized 13 individuals with biallelic TSPEAR variants. Individuals underwent either exome sequencing or panel‐based genetic testing. Nearly all of these newly reported individuals (11/13) have phenotypes that include tooth agenesis or ectodermal dysplasia, while three newly reported individuals have hearing loss. Of the individuals displaying hearing loss, all have additional variants in other hearing‐loss‐associated genes, specifically TMPRSS3, GJB2, and GJB6, that present competing candidates for their hearing loss phenotype. When presented alongside previous reports, the overall evidence supports the association of TSPEAR variants with ectodermal dysplasia and tooth agenesis features but creates significant doubt as to whether TSPEAR variants are a monogenic cause of hearing loss. Further functional evidence is needed to evaluate this phenotypic association.